Importancia de la sentencia nro. 253-20-JH de la Corte Constitucional para el reconocimiento de los animales silvestres como sujetos de derechos: Alcances y límites - Aguirre Sevilla, Martín Josué (2024)
The relationship between humans and animals has evolved over the course of history, going from being considered mere things, resources or property, to recognizing their intrinsic value and their capacity to be sentient beings, within the Constitution of the Republic of Ecuador in 2008 recognizes nature as a subject of rights, but without establishing what it comprises or what is considered Nature, the Constitutional Court, based on a habeas corpus action filed on behalf of a wild animal, recognizes wild animals as subjects of rights in extension to the rights that Nature possesses. Thus, the objective of the research was to study the importance of ruling No. 253-20-JH issued by the Constitutional Court for the recognition of wild animals as subjects of rights, through its hermeneutical analysis that allows specifying its scope and limits, in order to establish how a wild animal can be subject to the use of a jurisdictional guarantee such as in this case Habeas Corpus, for which, the research methods were used: normativist, hermeneutic and the synthetic analytical method with the purpose of carrying out logical operations of the analysis of the sentence and the elaboration of results. The research used the documentary review and analysis technique to facilitate this work. In this way, it was possible to reach the conclusion that although within the sentence issued by the Constitutional Court the use of habeas corpus in favor of the specimen is not appropriate because it had previously died, the Court sets a precedent in the history of environmental law and animal protection, establishing the use of any jurisdictional guarantee in order to demand the rights of nature and its elements.